Enhancing UV-emissions through optical and electronic dual-function tuning of Ag nanoparticles hybridized with n-ZnO nanorods/p-GaN heterojunction light-emitting diodes. Issue 8 (8th February 2016) - Yao, Yung-Chi; Yang, Zu-Po; Hwang, Jung-Min; Chuang, Yi-Lun; Lin, Chia-Ching; Haung, Jing-Yu; Chou, Chun-Yang; Sheu, Jinn-Kong; Tsai, Meng-Tsan; Lee, Ya-Ju
Abstract : We demonstrate Ag NP-incorporated n-ZnO NRs/p-GaN heterojunctions by facilely and hydrothermally growing ZnO NRs on Ag NP-covered GaN. Abstract : ZnO nanorods (NRs) and Ag nanoparticles (NPs) are known to enhance the luminescence of light-emitting diodes (LEDs) through the high directionality of waveguide mode transmission and efficient energy transfer of localized surface plasmon (LSP) resonances, respectively. In this work, we have demonstrated Ag NP-incorporated n-ZnO NRs/p-GaN heterojunctions by facilely hydrothermally growing ZnO NRs on Ag NP-covered GaN, in which the Ag NPs were introduced and randomly distributed on the p-GaN surface to excite the LSP resonances. Compared with the reference LED, the light-output power of the near-band-edge (NBE) emission (ZnO, λ = 380 nm) of our hybridized structure is increased almost 1.5–2 times and can be further modified in a controlled manner by varying the surface morphology of the surrounding medium of the Ag NPs. The improved light-output power is mainly attributed to the LSP resonance between the NBE emission of ZnO NRs and LSPs in Ag NPs. We also observed different behaviors in the electroluminescence (EL) spectra as the injection current increases for the treatment and reference LEDs. This observation might be attributed to the modification of the energy band diagram for introducing Ag NPs at the interface between n-ZnO NRs and p-GaN. Our results pave the way for developing advanced nanostructured LED devices with high luminescence efficiency in the UV emission regime.